Agama dan Dialektika Toleransi-Intoleransi: Analisis Kritis atas Dinamika Keagamaan dalam Masyarakat Plural Indonesia: Religion and the Dialectics of Tolerance and Intolerance: A Critical Analysis of Religious Dynamics in Pluralistic Indonesian Society - Akbar, Muchammad Fariz Maulana (Tashwirul Afkar, 2024)
In the context of a pluralistic society like Indonesia, religion plays an ambivalent role: on the one hand, it serves as a source of humanistic values, tolerance, and peace; on the other hand, it can be used to justify intolerance, discrimination, and even violence. This article argues that religious tolerance and intolerance are not inherent to religious teachings but result from the dynamic interplay between internal factors—such as theology, scriptural interpretation, and religious leadership—and external factors, including identity politics, economic inequality, and the rise of social media. Employing Peter L. Berger’s social construction theory and Johan Galtung’s conflict theory, this article highlights the importance of contextual interpretation, structural justice, and interfaith tolerance education as essential foundations for achieving positive peace. The findings reveal that without interpretive reform and broader social transformation, the potential for religion-based intolerance will continue to recur in various forms. Therefore, synergy between religious leaders, the state, and civil society is essential to building an inclusive and peaceful religious life in Indonesia.